Increasing Agricultural Production through Optimal use of Harvested Rainwater in Semi-arid Region - Khandelwal, M K; Shakya, S K; Narda, N K; Khepar, S D (Journal of Agricultural Engineering, 2002)
A situation specific computer programme incorporates hydraulic design and hydrological criteria, set of different runoff coefficients, and USDA, SCS, CN method to design parameters for water harvesting structures. The computer programme is used with average of the daily rainfall time (1971-97) to compute probable quantity of water that could be available by the end of estimated date of harvest. Recommended agronomic measures (crop coefficient, dates of sowing & harvest, duration, critical crop growth stages) for the specified regions are considered to compute water requirement and irrigation scheduling (at 66.67% field application efficiency) of prevailing crops in the regions under a variety of conditions (i) no deficiency of irrigation water (ii) yield reduction by 10%, and (iii) yield reduction by 20%. Gross returns, net returns on cost of cultivation and output input ratio at cost 'A' of all the prevailing crops (based on average of data 1980-81 to 1997-98), water requirements of crops and probable available water in the structure by the end of estimated date of harvest are used to formulate the linear programming problems which have been solved by stepwise optimization technique. The results suggest a set of optimal plans (alternatives) for cultivation during either Kharif or Rabi only, under different specific conditions. Application of the problems to an existing irrigation tank 'B' and comparison of the results reveal similar crops selection for cultivation during both the seasons. These solutions can also be adopted for better agricultural production under similar situations elsewhere.